SYNERGETICS: PROBLEMS AND OPPORTUNITIES IN THE RESEARCH OF SOCIAL SYSTEMS (Scientific journal of the Fergana State University, 2023)
The article describes the features of the use of synergetic ideas in the social sciences. Synergetics and its possibilities in the study of the social system are also discussed in detail. The development process is described by dialectics and cannot be replaced by synergetics. It has been studied that a more effective approach to the study of society in modern science can be carried out on the basis of a synthesis of elements of all existing methodological approaches, in particular: dialectical, informational, systemic, synergetic, etc.